Development of a Virtual Laboratory Platform to Enhance Chemistry Practical Learning in Higher Education - Rafiq Abrisam Iswan (Institute of Accounting Research and Novation (IARN), 2024)
This research explores the development of a virtual laboratory platform designed to support chemistry practical learning in higher education. The traditional laboratory setup often faces challenges such as limited access, safety concerns, and high operational costs, making it difficult for all students to fully engage in hands-on learning experiences. To address these issues, a virtual lab prototype was developed to provide an interactive, scalable, and accessible alternative for conducting chemistry experiments. The platform was designed with features such as step-by-step procedural guides, real-time feedback, and realistic simulations of common chemistry experiments. The effectiveness of the virtual lab was evaluated through a pilot implementation involving undergraduate chemistry students. Results showed a significant improvement in students' understanding of experimental concepts, with post-test scores increasing by 20% compared to pre-test scores. Feedback from students and instructors highlighted the platform's user-friendliness, accessibility, and the ability to visualize complex chemical processes. The research also identified areas for improvement, including the need for more advanced simulations and enhanced data tracking for instructors. Overall, the virtual laboratory platform demonstrated potential as an effective tool for enhancing practical chemistry education. It offers an inclusive and cost-effective solution that complements traditional laboratory work, making it a valuable resource for higher education institutions seeking to overcome the limitations of physical labs. Future developments of the platform will focus on expanding the range of experiments, improving technical performance, and incorporating more advanced features based on user feedback.